Segregasi Niche antara Oreochromis mossambicus dan Oreochromis niloticus Di Sungai Banjaran, Kabupaten Banyumas - Lestari, Windiariani; Kustama, Abttsa Alhaz; Suryaningsih, Suhestri; Sriwijayati, Monik (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
Alien fish are introduced to diversify farmed fish, ornamental fish, or disease vector controllers. Alien fish in aquatic generally becomes a threat for indegenous fish as competitors for food, space and as predators. This will affect fish structure populations and results in niche segregation (space utilization) to avoid competition. Niche segregation encourages certain fish to occupy niches spatial and temporal diferently. Niche segregation may also occur between O. mossambicus and O. niloticus in the Banjaran River. This research was done by using a survey method with the Purposive Random Sampling technique. Sampling was conducted at five selected stations along Banjaran River every two weeks from July until September 2018. Research variables were O. mossambicus and O. niloticus populations with parameters abundance, length and weight of fish The supporting variable was water quality with the physical parameters were temperature, brightness, and current and the chemical parameter were dissolved oxygen (DO) content, biochemical oxygen demand (BOD), chemical oxygen demand (COD), and also potential hydrogen (pH). Data on fish population structure and niche segregation were analyzed descriptively. Correlation between physical-chemical aquatic factors and fish abundances were analyzed using PCA (Principal Component Analysis). The result showed that the O. mossambicus population was more than O. niloticus. The abundance of O. mossambicus in the five stations were different (p: 0.005), while the abundance of O. niloticus were relatively the similar (p: 0.184). There were differences in length distribution of O. mossambicus (p: 6.934E-09) and O. niloticus (6.174E-05) at five stations. The weight distribution of O. mossambicus at five stations was significantly different (p: 3.609E-09), and the weight distribution of O. niloticus (p: 6.631E-05) was also different. The temporal niche segregation between O. mossambicus and O. niloticus was recorded in stasiun 5. The abundances of O. mossambicus and O. niloticus were negatively correlated to the physical and chemical factors of the water quality of Banjaran River